Negative Sestamibi Scans Predict Lower Likelihood of Surgical Referral in Patients with Primary Hyperparathyroidism. Issue 8 (August 2018) - Lloyd, Jacob Q.; Holcombe, Jenny M.; Rackley, Allyssa A.; Tanner, Richard M.; Giles, W. Heath
99m Technetium sestamibi scans (MIBI) can provide negative or inaccurate results in patients with biochemical primary hyperparathyroidism. Reliance on MIBI as a diagnostic modality rather than as a localization tool leads to misdiagnosis and inappropriate care. The aim of this study was to determine the impact of negative MIBI scans on referral patterns and surgical intervention. Adults with MIBI scans at our institution from January 1, 2011, to May 31, 2017, were retrospectively reviewed. Data collected include demographics, study date and results, ordering physician specialty, pre/postoperative laboratories, and operative and final pathology. Statistical analysis was performed with SPSS v24 (IBM Corp., Armonk, NY). Three hundred fifty-seven patients had a MIBI scan; 10 were excluded for incomplete data or incorrect diagnosis. One hundred eighty-six were interpreted as positive (53.6%) and 161 were interpreted as negative (46.4%). Of the 186 positive MIBI scans, 135 (72.6%) were seen by an endocrine surgeon (ES). Of these 135 patients, 111 (82.2%) underwent parathyroidectomy. Of the 161 negative MIBI scans, 69 (42.9%) were seen by an ES. Of these, 53 (76.8%) underwent parathyroidectomy. In all, 90/92 (97.8%) with a negative MIBI scan who were not seen by an ES did not have surgery. Nonendocrine surgeon physicians are more likely to use MIBI scans as diagnostic tools to assist with clinical decision-making. Patients with a negative MIBI scan not seen by an ES were significantly less likely to undergo para-thyroidectomy. Patients with primary hyperparathyroidism should be referred to an experienced parathyroid surgeon for evaluation, regardless of the MIBI result.